(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Internet has grown in the past and has transformed several fields and changed numerous lives. Internet can be a blessing for humanity. The primary field that has been transformed by internet technology is communication. Internet has allowed speedier and simpler communication. In this paper, we intend to explore the various methods for conversion of speech-to-text that can be utilized in an email system that is based on voice. This method is built on the interactive voice response. The goal is to research and evaluate the different methods that are used in STT conversions, and find the most efficient method that is able to be adapted to both conversion processes. In the end, based on a review study, it has been discovered that HMM using deep neural networks is the most effective statistical model , and therefore the best for STT. In the end, a model that uses HMM and ANN techniques to convert STT conversion is suggested.